2018
DOI: 10.1128/jvi.00921-17
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Adaptation of a Novel Highly Pathogenic H7N9 Influenza Virus in Birds and Humans from a 2013 Human-Infecting Low-Pathogenic Ancestor

Abstract: Since its emergence in 2013, the H7N9 low-pathogenic avian influenza virus (LPAIV) has been circulating in domestic poultry in China, causing five waves of human infections. A novel H7N9 highly pathogenic avian influenza virus (HPAIV) variant possessing multiple basic amino acids at the cleavage site of the hemagglutinin (HA) protein was first reported in two cases of human infection in January 2017. More seriously, those novel H7N9 HPAIV variants have been transmitted and caused outbreaks on poultry farms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 27 publications
1
109
0
Order By: Relevance
“…We previously reported that the H7N9 highly pathogenic virus was not lethal in mice (Shi et al, 2017), but other groups reported that some chicken H7N9 highly pathogenic viruses had killed certain mice after inoculation with 10 6 50% egg infectious dose (EID 50 ) of virus (Liu et al, 2018; Qi et al, 2018). H7N9 viruses with four different motifs in their HA cleavage sites were all highly lethal in chickens (Shi et al, 2017); however, it is not known whether differences in these motifs affect the virulence of the viruses in mammals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the H7N9 highly pathogenic virus was not lethal in mice (Shi et al, 2017), but other groups reported that some chicken H7N9 highly pathogenic viruses had killed certain mice after inoculation with 10 6 50% egg infectious dose (EID 50 ) of virus (Liu et al, 2018; Qi et al, 2018). H7N9 viruses with four different motifs in their HA cleavage sites were all highly lethal in chickens (Shi et al, 2017); however, it is not known whether differences in these motifs affect the virulence of the viruses in mammals.…”
Section: Resultsmentioning
confidence: 99%
“…Avian and human H7N9 viruses were able to bind to both avian-type and human-type receptors (Belser et al, 2013; Richard et al, 2013; Watanabe et al, 2013; Zhou et al, 2013), but the human isolates were more lethal in mice and more transmissible in ferrets than the avian isolates (Zhang et al, 2013). In early 2017, a few H7N9 HA mutants were detected from samples collected in the live poultry markets in Guangdong province, and animal studies indicated that these mutants were highly pathogenic for chickens (Qi et al, 2018; Shi et al, 2017). Although the index H7N9 HA mutant was not lethal in mice or ferrets, our previous study (Shi et al, 2017) and a study performed by Imai et al (Imai et al, 2017) revealed that the H7N9 HA mutants could acquire additional mutations during their replication in ferrets or humans, and then become highly lethal in mammals and transmissible in ferrets by respiratory droplet.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, viruses of human origin were more pathogenic in mice than avian viruses. Now, these novel HPAI H7N9 strains have caused human infection in 3 provinces and poultry farm outbreaks in 8 provinces [6]. Considering the rapid geographical expansion of the HPAI H7N9 viruses, effective control measures are urgently needed [7].…”
Section: Introductionmentioning
confidence: 99%
“…To date, most evidence supports the notion that the insertion event probably occurred in poultry in the Pearl River Delta region and that the Guangdong Province was the original location of the HPAI H7N9 virus . The HPAI H7N9 virus might have emerged in mid‐2016, according to a molecular clock model .…”
Section: Introductionmentioning
confidence: 74%
“…In early 2017, human infections with a highly pathogenic avian influenza (HPAI) A(H7N9) virus were reported in Taiwan and Guangdong Provinces of China . Phylogenic analyses showed that the HPAI H7N9 virus originated from the LPAI H7N9 virus . The signature genetic difference between HPAI and LPAI H7N9 virus was an insertion of four amino acids at the cleavage site of the HA protein .…”
Section: Introductionmentioning
confidence: 99%